INTERELASI ISLAM DAN BUDAYA: STUDI TRADISI UPAH-UPAH DI ASAHAN, SUMATERA UTARA - Lubis, Ihza Nurfadli Ramadhan (Institut Agama Islam Ngawi, 2024)
Upah-upah is a tradition that developed on the East coast of North Sumatra. This tradition functions as a tool to express oneself in celebrations in Malay society, especially in Asahan, North Sumatra. In essence, this tradition does not only originate from the coast which is actually Muslim but is also carried out by the mountainous communities of North Sumatra who are non-Islamic. The initial emergence of this tradition was the same as the traditions that developed in society in general, namely that it was not far from